Annual Plan 2002-03 - Planning Commission (Planning Commission, 2002)
The Approach Paper to the Tenth Five Year Plan was formulated in the context of the Prime Minister’s vision of doubling per capita income in the country within the next ten years. Hence, the Plan aims at achieving an economic growth target of 8 per cent average GDP growth for the period 2002-07 as the first step towards fulfilling the ultimate aim of doubling per capita income by 2012. The Approach Paper also recognized that economic growth cannot be the only objective of national planning and the development objectives should be specified in the broader sense of enhancement of human well-being.
Planning Commission Government of India
Planning Commission Government of India